Simultaneously defining cell phenotypes, cell cycle, and chromatin modifications at single‐cell resolution. Issue 7 (28th March 2013) - Chambliss, Allison B.; Wu, Pei‐Hsun; Chen, Wei‐Chiang; Sun, Sean X.; Wirtz, Denis
Abstract : Heterogeneity of cellular phenotypes in asynchronous cell populations placed in the same biochemical and biophysical environment may depend on cell cycle and chromatin modifications; however, no current method can measure these properties at single‐cell resolution simultaneously and in situ. Here, we develop, test, and validate a new microscopy assay that rapidly quantifies global acetylation on histone H3 and measures a wide range of cell and nuclear properties, including cell and nuclear morphology descriptors, cell‐cycle phase, and F‐actin content of thousands of cells simultaneously, without cell detachment from their substrate, at single‐cell resolution. These measurements show that isogenic, isotypic cells of identical DNA content and the same cell‐cycle phase can still display large variations in H3 acetylation and that these variations predict specific phenotypic variations, in particular, nuclear size and actin cytoskeleton content, but not cell shape. The dependence of cell and nuclear properties on cell‐cycle phase is assessed without artifact‐prone cell synchronization. To further demonstrate its versatility, this assay is used to quantify the complex interplay among cell cycle, epigenetic modifications, and phenotypic variations following pharmacological treatments affecting DNA integrity, cell cycle, and inhibiting chromatin‐modifying enzymes.—Chambliss, A. B., Wu, P.‐H., Chen, W.‐C., Sun, S. X., Wirtz, D. Simultaneously defining cell phenotypes, cell cycle, and chromatin modifications at single‐cell resolution. FASEB J. 27, 2667‐2676 (2013). www.fasebj.org